Accelerometer-determined physical activity level in adults with abdominal obesity. - Heng, Kiang Soon; Abu Saad, Hazizi; Mohd Taib, Mohd Nasir; Abdul Rahman, Hejar; Chan, Yoke Mun (2011)
A cross-sectional study was carried out to assess the physical activity level among 201 adults with abdominal obesity at the Universiti Putra Malaysia, Malaysia. Socio-demographic information, anthropometric data, blood pressure and lipoprotein-lipid proˆles were collected. Steps/day and energy expenditure were determined by Lifecorder e-Step accelerometer. Mean steps/day of the subjects was 6420±2283. The total daily energy expenditure (TDEE) averaged 2015±307 kcal. Based on step counts, 91.5%of the subjects fell below the ``active'' category but based on physical activity level (PAL), 97.0%fell under the ``low active'' or ``sedentary'' . Individuals with abdominal obesity in this study were relatively sedentary. Signiˆcant positive correlations were found between TDEE and body mass index (men: r＝0.428, p＝0.0001; women: r＝0.556, p＝ 0.0001), waist circumference (men: r＝0.508, p＝0.0001; women: r＝0.340, p＝0.0001) and percentage of body fat (men: r＝0.261, 0.028; women: r＝0.414, 0.0001). There was an inverse relationship between physical activity level and the odds of having metabolic syndrome. However, most of the variables studied did not vary between physical activity categories.